Nutritional characteristics of soil and leaves in the cultivation of Plectranthus amboinicus (Lour.) Spreng (Research, Society and Development, 2021)
Plectranthus amboinicus (Lour.) Spreng., from the Lamiaceae family, has therapeutic and nutritional properties attributed to its natural phytochemicals, which are highly valued in the pharmaceutical industry. The objective of the study was to evaluate the nutritional conditions offered by two types of organic fertilizers in the cultivation of this species and to verify the use of these nutrients by the leaves of the vegetable. The research was carried out with fertilization of associated poultry and bovine manure (Treatment A) and fertilization only with bovine manure (Treatment B). Soil properties were measured in relation to: pH, sum of bases (SB), assortment complex, available content of phosphorus, sulfur and micronutrients, saturation of the assortment complex by bases and cation exchange capacity (CTC). In leaf diagnosis, the determination of macronutrient and micronutrient contents was performed. Treatment B increased the levels of Ca and Mg, SB and CTC in the soil. Treatment A increased the levels of P, Fe, Mn and Cu in the soil and N (30.8 g/kg), P (4.9 g/kg), B (59 mg/dm3), Cu (19,1 mg/dm3), Fe (615 mg/dm3) and Zn (57 mg/dm3) in the leaves of Plectranthus amboinicus. There was an improvement in the nutritional content of the leaves of the species under study by the use of poultry manure associated with bovine manure in soil fertilization.